Hubungan antara Kecemasan dengan Aktivitas dan Fungsi Seksual pada Wanita Usia Lanjut di Kabupaten Purworejo - Lidia Hastuti, Muhammad Hakimi, Djaswadi Dasuki (Berita Kedokteran Masyarakat (BKM), 2008)
Background: the decline of physical functions in older women specially the organs regarding to their sexuality functions causes the changes on sexual responses at all phases (desire, plateau, orgasms and resolution phases). Despite physiological factors, psychological factors such as anxiety can result in disorders in their sexual activity and function. Until recently, studies on sexual activity and function in old women are still rare so that a good study on the issue is needed.Objective: this study was undertaken to know the association between anxiety and sexual activity and function among older women.Method:  it was an observational study with cross-sectional design. The subjects selected by cluster random sampling were 6,698 women over 50 years of age obtained from the data of  longitudinal surveillance from CHN-RL, Faculty of Medicine, GMU in Purworejo District. The study instrument used was SAGE developed by WHO and the data analysis used was Stata program version 8. The hypothesis test was done by using multinominal logistic regression test.Results: from the respondents observed, the women that still did sexual activity were 38.52% with the sexual dysfunction prevalence of 45.20% and the anxiety prevalence of 34.92%. Anxiety increased the risk of sexual dysfunction 1.5 times (OR=1.5 95%CI 1.4 – 1.9). Anxiety also increased the dissatisfaction in older women’s sexual life 1.1 times (OR=1.5 95%CI 1 – 1.3). Anxiety old women experienced declining of sexual frequency with OR of 1.2 for the activity frequency ‘occasionally’ and 0.7 for the activity frequency ‘often’.Conclusion: anxiety in older women increased the risk of sexual dysfunction, dissatisfaction in sexual life and decreased the frequency of sexual activity. Other factor such as age, educational level, marital status, parity, heart disease and diabetes mellitus were other risk factors in old women’s sexual dysfunction.Keywords: anxiety, activity and sexual function, older woman